Effectiveness Analysis of Safety Barrier in Reducing The Risk of Fatality on The Toll Road - FREDDY (NIM: 25016052), MICHAEL
Safety barrier serves to minimize the impact of collisions with hazard on the roadside. However, in reality there is still fatalities when vehicle crash to safety barrier. Therefore, this research aims to study about the effectiveness of the rigid barrier and guardrail in preventing the fatality when accident occurs on the toll road, compared with conditions without safety barrier. A binary logistic regression model was then developed to relate fatality with the variables influenced it. The result shows that fatality of accident are related to the type of safety barrier hit and vehicle type involved in the crash. This study concludes that guardrail is the most effective safety barrier in preventing fatality of accident and rigid barrier is the least effective in preventing fatality of accident, even whem compared to condition without barrier installed at the crash site. This inaccuracies may be due to the independat variable used in the model, which only vehicle type and barrier types, and ignoring the other variables that involved when the accident happened.